Keragaman dan komposisi jenis bibit untuk rehabilitasi hutan dan lahan (RHL) di Derah Aliran Sungai (DAS) Kapuas - Wiryono, Wiryono; Nurliana, Steffanie (Naturalis: Jurnal Penelitian Pengelolaan Sumberdaya Alam dan Lingkungan, 2023)
Indonesia has extensive degraded land to be rehabilitated. This study aimed to analyze the species diversity and composition of seedlings for land rehabilitation in Kapuas Watershed, the reasons for species selection, and the location of seedling plantation and to compare the species compostion of seedlings for rehabilitation of degraded lnad in Kapuas Watershed dan Serayu-Opak-Progo Watershed. Three-year (2015-2016-2017) data of seedlings were gathered through questionnaire to Kapuas Watershed Management Agency. The data were analyzed quantitatively using a statistical software called Past. The results showed that the species richness of seedlings ecah year ranged from 15-25 eitth a total of total species of 34, consisting of 24 native species and 10 introduced. The Simpson dominance index (D) was 0.19-0.93, Simpson diversity index (1-D) 0.07- 0.81, and Shannon diversity index (H’) 0.22-1.97. The selection of species was mostly determined by its high availability and most of the seedlings were planted in forest area. The composition of seedling species in Kapuas Watershed had low similarity with that of Serayu-Opak-Progo Watershed. The resulted vegetation would have moderately diverse species.